The Evaluation of the Use of Line Webtoon: A Development Study - Mery Berlian; Iqbal Miftakhul Mujtahid (Action Research Journal Indonesia (ARJI), 2025)
Webtoon is a popular Line Webtoon platform in Indonesia that can be used as education and information media among the users. The Internet users make the information that is available in webtoon can be spread to all Indonesian people since webtoon applies the online-based comic system. Through this webtoon comic, it is expected that it can justify the wrong perception of open university to the users. Consequently, it can improve the users’ motivation and interest to continue their study at open university. This study uses a quantitative research design with a survey method. A survey study had been conducted toward 55 users. Data collection technique was done by distributing online questionnaires, and then, the data were analyzed by using quantitative data analysis assisted by SPSS version 23.00 for Windows. Based on the result and the discussion of the study that had been revealed previously, it can be drawn a conclusion that line webtoon as education media in increasing the users’ interest and motivation developed using the ADDIE model has been successfully developed and published; therefore, it can be widely used. Also, the use of webtoon among the users in Riau province as education media is categorized as good (3.09). It can be seen from the eight components, namely didactic component (2.93); webtoon construction (3.13); the technique of webtoon (3.20); ease of use (3.13); the efficiency of webtoon (3.11); benefits (3.13); interests (3.07); and motivation (3.04). These findings make an important contribution that popular digital-based media, such as webtoons, can be an innovative alternative in supporting the learning process. The main implication is that teachers and education practitioners can leverage webtoons to increase student engagement, motivation, and interest in learning because this medium is close to their daily lives.